Perspectives on Principal Leadership Capacities: Evidence from Secondary Schools in Sri Lanka - Nanayakkara Godewasam Liyanage, Sithara Jayamali Liyanage (Journal of Research, Innovation, and Strategies for Education (RISE), 2026)
This study investigated teachers’ perceptions of principals’ leadership capacities in secondary schools within the Galle Educational Division, Sri Lanka. Grounded in transformational and distributed leadership theories, the research explored how teachers evaluated their principals’ competencies across five dimensions: shared vision for high student achievement, instructional leadership, staff professional development and guidance, personal leadership qualities, and systems and resource management. A descriptive survey design was employed, involving 85 teachers randomly selected from ten schools representing diverse contexts. Data were collected using a self-structured questionnaire and analyzed primarily through descriptive statistics and Chi-square tests to identify variations in perceptions across demographic factors such as gender and age. Findings revealed that teachers generally perceived principals positively in personal leadership qualities and shared vision, while comparatively lower ratings were observed in areas related to staff professional development and instructional leadership. Gender-based analysis indicated minor perceptual differences, with female teachers showing slightly higher levels of satisfaction with leadership practices. The study highlights the contextual and relational nature of effective school leadership within Sri Lanka’s centralized education system. It concludes that developing principals’ instructional and mentoring capacities through targeted professional development programs is critical for enhancing school effectiveness. The findings contribute empirical insights to the limited body of research on educational leadership in South Asian contexts and inform leadership training and policy reforms in Sri Lanka.